Load Frequency Control in Smart Grids: A Review of Recent Developments - Wadi, Mohammed; Shobole, Abdulfetah; ELMASRY, WİSAM; Küçük, İsmail (Elsevier Ltd., 2024)
This study provides a comprehensive and fresh review of load frequency control (LFC) in multi-area interconnected power systems (MAIPSs). The central tasks of LFC are to keep frequency variations as minimum as possible to achieve an acceptable level of stability. This research provides a complete view, from early classical control to recent technologies and modern techniques considering strategies, robust, optimal, self-tuning, and adaptive controllers for LFC in MAIPSs. Fuzzy control and earlier and recent optimization algorithms also are analyzed. The linearity, nonlinearity, and uncertainty of LFC models are also investigated. This review emphasizes recent technological advances and novel control strategies. LFC is also considered with the integration of wind, photovoltaic, electric vehicles, and storage devices. Besides, the utilization of machine learning and reinforcement techniques is examined. Further, LFC in smart grids and modern complex power systems concerning limited communication bandwidth, communication failure, and cyber-attacks are also investigated. This review provides an in-depth and detailed diagnosis of the challenges associated with LFC in modern and complex power systems. This work may be valuable for studies and practitioners interested in LFC. It, in detail, investigates future efforts and directions to enhance LFC performance, stability, and reliability in the face of increasing complexity and uncertainty. © 2023 Elsevier Ltd
Keywords: Artificial intelligence (AI); Communications failures; Cyber attacks; Electric vehicles (EVs); Load frequency control (LFC); Multi-area interconnected power system (MAIPS); Optimization algorithms; Renewable energy; Smart grids